Optimal planting density for cut Lilium and tuberose production - Ahmad, Iftikhar; Naeem, Waqas Hassain; Abdullah, Bilal (Ornamental Horticulture, 2019)
Lilium and tuberose are promising geophytic flowers, which have high market demand in global floral markets. A study was conducted to optimize planting densities for cut lilium and tuberose production. Bulbs of Asiatic lily ‘Brunello’ and tuberose ‘Single’ were planted on 7.5 cm, 15.0 cm and 22.5 cm between bulbs while ridge were spaced at 60 cm apart. Lilium bulbs planted at 22.5 cm took 185 d, while tuberose took 101 d to produce flowers as compared to 7.5 cm spacing (173 d and 93 d, respectively). Bulbs of lilium and tuberose planted at 22.5 cm resulted in tallest plants with highest leaf area for both tested species, 69.1 cm and 11.4 cm2 for lilium and 110.6 cm and 30.2 cm2 for tuberose, respectively. Both species had highest number of florets with longer stem/ spike length and stem/spike diameter when planted 22.5 cm apart, while close planting further decrease number of buds/florets and stem/spike length. Similar results were recorded for fresh weight of a stem, while vase life and dry weight of a stem were relatively less affected by plant spacing. However, lilium and tuberose bulbs when planted at 22.5 cm plant spacing produced higher number of best quality stems for market as compared to other planting densities.